Special Education during times of dictatorship - Katia Regina Moreno Caiado; Maria Edith Romano Siems-Marcondes; Marcia Denise Pletsch (Arizona State University, 2019)
The texts of this dossier analyze the role played by different political and social actors in the institutionalization of Special Education in Brazil during the civil-military dictatorship (1964-1985), with emphasis on the theoretical and political debates that influenced the agents' stance. The dossier also brings a paper that discusses the institutionalization of Special Education in Italy during the 1970s, thus contributing to the construction of comparisons and theoretical and methodological breakthrough in the area of Special Education History. It is hoped that the papers presented in this dossier raise questions and reflections on the proposals that have been gaining ground in Brazil, which are again focusing on assistentialist perspectives that link disability to the medical model, rather than on a social model and rights of this population.